MYH2 myopathy, a new case expands the clinical and pathological spectrum of the recessive form - Telese, Roberta (Mol Genet Genomic Med, 2020)
BACKGROUND: Hereditary myosin myopathies are a group of rare muscle disorders, caused by mutations in genes encoding for skeletal myosin heavy chains (MyHCs). MyHCIIa is encoded by MYH2 and is expressed in fast type 2A and 2B muscle fibers. MYH2 mutations are responsible for an autosomal dominant (AD) progressive myopathy, characterized by the presence of rimmed vacuoles and by a reduction in the number and size of type 2A fibers, and a recessive early onset myopathy characterized by complete loss of type 2A fibers. Recently, a patient with a homozygous mutation but presenting a dominant phenotype has been reported. METHODS: The patient was examined thoroughly and two muscle biopsies were performed through the years. NGS followed by confirmation in Sanger sequencing was used to identify the genetic cause. RESULTS: We describe the second case presenting with late‐onset ophthalmoparesis, ptosis, diffuse muscle weakness, and histopathological features typical for AD forms but with a recessive MYH2 genotype. CONCLUSION: This report contributes to expand the clinical and genetic spectrum of MYH2 myopathies and to increase the awareness of these very rare diseases.